Pilot Experience on the Use of S53P4 Bioactive Glass in the Surgical Management of Diabetic Foot Osteomyelitis. (March 2022) - Iacopi, Elisabetta; Pieruzzi, Letizia; Goretti, Chiara; Piaggesi, Alberto
To test safety and efficacy of bioactive glass, a novel material used to replace bone, able to completely bond itself to the host tissues on patients treated for osteomyelitis (OM) complicating a diabetic foot (DF). We evaluated a group of patients consecutively admitted in our department between September and December 2018, who underwent surgical DF procedures for OM and in whom the use of bioactive glass could limit the demolition phase of surgical procedure. Patients were treated with bioactive glass S53P4 on top of standard treatment directly in operating room. The patients were weekly controlled for 6 months or until complete healing. During follow-up, we analyzed primarily healing rate and secondarily time of healing, need for further debridement procedures, recurrences, and adverse or hypersensitivity reactions to study treatment. Ten DF patients were enrolled (male/female 6/4; mean age 56 ± 11 years; mean duration of diabetes 10.5 ± 4.7 years, mean hemoglobin A1c 7.2 ± 0.9%). Patients underwent surgical procedure during which, after an accurate debridement, bioactive glass was applied. A healing rate of 80% in a mean time of 34 ± 2 days, with only 1 patient who needed a second surgical look, was observed. Neither recurrences nor adverse events during follow-up were observed in treated patients. This pilot experience demonstrated that bioactive glass can be considered a useful tool for the surgical treatment of DF-related OM.